Comparing Multiplex PCR and Rapid Urease Test in the Detection of H. pylori in Patients on Proton Pump Inhibitors - Thomas Chen; Xiangwen Meng; H. Zhang; Rebecca W. Tsang; Tat-Kin Tsang (Gastroenterology Research and Practice)
Background. This study was conducted to assess the diagnostic value of a multiplex PCR assay to detect H. pylori infection and to further evaluate the negative results from the CLOtest on patients with and without PPI treatment. Methods. This study is a retrospective cohort that included 457 patients with symptoms of dyspepsia, who underwent upper endoscopy at Evanston and Glenbrook Northshore Hospital from June 2003 to October 2007. A total of 556 samples were reported with some patients having more than one test over the time period. The CLOtest was performed first on the gastric specimen and from that specimen, the DNA was isolated and the one-step multiplex PCR was performed. Results. By M-PCR testing, H. pylori was detected in 143 (52.2%) of 274 cases in the control group and 130 (46.1%) of 282 cases in patients on PPI treatment (P=0.1746). The CLOtest detected the presence of H. pylori in 4 (1.4%) of 282 cases from the same group receiving PPI treatment and 29 (10.6%) of 274 cases from the group not taking a PPI (P≤0.0001). Conclusion. Our PCR is sensitive enough to detect the presence of H. pylori despite being on PPI treatment.